Cuidado de enfermagem à pessoa com paraplegia fundamentado no modelo Roper-Logan-Tierney - Cavalcante, Karenine Maria Holanda (2007)
The Spinal Cord Injury (SCI) is one of the main causes of serious sequels in trauma patient. After any type of spinal cord injury, the person will need to face a detailed process of rehabilitation, to reacquire the capacity to do its activities of life, and to live in independent way. The aim of this study was to analyze the effectiveness of the nursing care based on the Model of Nursing Roper-Logan-Tierney to people with spinal cord injury, as well as, knowing the contribution of the use of a theoretical model for the care directed to people with SCI in their home. It is a convergent-assistencial research. The participants of the study had been three people, two women and a man, with paraplegia, which are enclosed in a cadastre of participants of researches made by NUPEN. The process of investigating and taking care happened by means of 10 domiciliary visits (for each participant). The meetings were based on the Model of Nursing Roper-Logan-Tierney, using the instrument considered by the authors, in which it was approached and identified the performance of the activities of life, detaching the real and potential problems to be drawn the plan of cares up and to be done the necessary interventions, keeping the constant evaluation. The participant observation, the informal interview and the structuralized interview had been used for getting the information. In the development of the care process, it had been used nursing diagnosis, NANDA, nursing outcomes, NOC, and nursing interventions, NIC. After sum up in detail the data, I tried to give meaning to some information about the performance of the activities of life, trying to contextualize them for expanding for the care directed to people with spinal cord injury. When I was analyzing the behavior of the three participant of the study, I understood that the biggest barrier for the effectiveness of the considered care is the difficulty for change habits; however, with the persistence and the use of clarifications and necessary information important results are gotten. Therefore, I point out the importance of the promotion of the self-responsibility for health, to fortify the search for changes in behaviors. The use of the theoretical model Roper-Logan-Tierney in the domiciliary care directed to these clients contributed intensely for the acquisition of the knowledge about behaviors and beliefs related to each activity of life and up against this, planning and implementing the care. So, the care process leaves of being generalized and becomes individualized, causing better results. It was possible to detect the effectiveness of this process of investigating and taking care, once it was well-known the resultant benefit, by means of the conquest of more independence and more ability to solve problems for the participants of the study and its family. Moreover, the use of a theoretical model for the care directed to people with spinal cord injury in home brought important contributions: it provided the systematization for the assistance, facilitating the approach to the person with paraplegia and its daily and effectiveness of the process of taking care considered for the research; and promoted a consistent theoretical basis for the development of the care.